Optimization of computed tomography pulmonary angiography protocols using 3D printed model with simulation of pulmonary embolism - Aldosari, S.; Jansen, S.; Sun, Zhonghua (AME Publishing Company, 2018)
Background: Three-dimensional (3D) printing has been shown to accurately replicate anatomical structures and pathologies in complex cardiovascular disease. Application of 3D printed models to simulate pulmonary arteries and pulmonary embolism (PE) could assist development of computed tomography pulmonary angiography (CTPA) protocols with low radiation dose, however, this has not been studied in the literature. The aim of this study was to investigate optimal CTPA protocols for detection of PE based on a 3D printed pulmonary model. Methods: A patient-specific 3D printed pulmonary artery model was generated with thrombus placed in both main pulmonary arteries to represent PE. The model was scanned with 128-slice dual-source CT with slice thickness of 1 and 0.5 mm reconstruction interval. The tube voltage was selected to range from 70, 80, 100 to 120 kVp, and pitch value from 0.9 to 2.2 and 3.2. Quantitative assessment of image quality in terms of signal-to-noise ratio (SNR) was measured in the main pulmonary arteries and within the thrombus regions to determine the relationship between image quality and scanning protocols. Both two-dimensional (2D) and 3D virtual intravascular endoscopy (VIE) images were generated to demonstrate pulmonary artery and thrombus appearances. Results: PE was successfully simulated in the 3D printed pulmonary artery model. There were no significant differences in SNR measured in the main pulmonary arteries with 100 and 120 kVp CTPA protocols (P>0.05), regardless of pitch value used. SNR was significantly lower in the high-pitch 3.2 protocols when compared to other protocols using 70 and 80 kVp (P<0.05). There were no significant differences in SNR measured within the thrombus among the 100 and 120 kVp protocols (P>0.05). For low dose 70 and 80 kVp protocols, SNR was significantly lower in the high-pitch of 3.2 protocols than that in other protocols with different pitch values (P<0.01). 2D images showed the pulmonary arteries and thrombus clearly, while 3D VIE demonstrated intraluminal appearances of pulmonary wall and thrombus in all protocols, except for the 70 kVp and pitch 3.2 protocol, with visualization of thrombus and pulmonary artery wall affected by artifact associated with high image noise. Radiation dose was reduced by up to 80% when lowering kVp from 120 to 100 and 80 kVp with use of 3.2 high-pitch protocol, without significantly affecting image quality. Conclusions: Low-dose CT pulmonary angiography can be achieved with use of low kVp (80 and 100) and high-pitch protocol with significant reduction in radiation dose while maintaining diagnostic images of PE. Use of high pitch, 3.2 in 70 kVp protocol should be avoided due to high image noise and poorer quality.